Joint Estimation of Balanced Motions and Internal Tides From Future Wide‐Swath Altimetry. (23rd December 2021) - Le Guillou, Florian; Lahaye, Noé; Ubelmann, Clément; Metref, Sammy; Cosme, Emmanuel; Ponte, Aurélien; Le Sommer, Julien; Blayo, Eric; Vidard, Arthur
Abstract: Wide‐swath altimetry, for example, the Surface Water and Ocean Topography mission is expected to provide Sea Surface Height (SSH) measurements resolving scales of a few tens of kilometers. Over a large fraction of the globe, the SSH signal at these scales is essentially a superposition of a component due to balanced motions (BMs) and another component due to internal tides (ITs). Several oceanographic applications require the separation of these components and their mapping on regular grids. For that purpose, the paper introduces an alternating minimization algorithm that iteratively implements two data assimilation techniques, each specific to the mapping of one component: a quasi‐geostrophic model with Back‐and‐Forth Nudging for BMs, and a linear shallow‐water model with 4‐Dimensional Variational assimilation for ITs. The algorithm is tested with Observation System Simulation Experiments where the truth is provided by a primitive‐equation ocean model in an idealized configuration simulating a turbulent jet and mode‐one ITs. The algorithm reconstructs almost 80% of the variance of BMs and ITs, the remaining 20% being mostly due to dynamics that cannot be described by the simple models used. Importantly, in addition to the reconstruction of stationary ITs, the amplitude and phase of nonstationary ITs are reconstructed. Sensitivity experiments show that the quality of reconstruction significantly depends upon the timing of observations. Although idealized, this study represents a step forward towards the disentanglement of BMs and ITs signals from real wide‐swath altimetry data. Plain Language Summary: Wide‐swath altimetry, for example, the Surface Water and Ocean Topography mission is expected to provide Sea Surface Height (SSH) images with pixels of 2 km, revealing motions at scales of a few tens of kilometers. At these scales, SSH variations are essentially due to the superposition of slow, balanced motions primarily constrain by Earth's rotation, and fast, propagating motions due to internal waves mainly generated by interactions between bathymetry and tidal water displacements. Several oceanographic applications require the separation of these two SSH components and their mapping on regular grids. This paper presents an original method to achieve this separation, based on data assimilation approaches and simple dynamical models. Experiments with synthetic SSH images, simulated from an ocean circulation model with detailed physics, show the efficiency of the method. Key Points: We present a dynamical method that estimates and separates balanced motions (BMs) and internal tides (ITs) from sea surface height data The method uses iteratively two data assimilation techniques, each specific to the estimation of one component (BMs or ITs) Although idealized, this study shows encouraging results for the disentanglement of BMs and ITs signature on future wide‐swath altimetry data